The strength of a remorseful heart: psychological and neural basis of how apology emolliates reactive aggression and promotes forgiveness - Beyens, Urielle; Yu, Hongbo; Han, Ting; Zhang, Li; Zhou, Xiaolin (Frontiers in Psychology, 2015)
Apology from the offender facilitates forgiveness and thus has the power to restore a broken relationship. Here we showed that apology from the offender not only reduces the victim’s propensity to react aggressively but also alters the victim’s implicit attitude and neural responses towards the offender. We adopted an interpersonal competitive game which consisted of two phases. In the first, “passive” phase, participants were punished by high or low pain stimulation chosen by the opponents when losing a trial. During the break, participants received a note from each of the opponents, one apologizing and the other not. The second, “active” phase involved a change of roles where participants could punish the two opponents when winning. Experiment 1 included an Implicit Association Test (IAT) in between the reception of notes and the second phase. Experiment 2 recorded participants’ brain potentials in the second phase. We found that participants reacted less aggressively towards the apologizing opponent than the non-apologizing opponent in the active phase. Moreover, female, but not male, participants responded faster in the IAT when positive and negative words were associated to the apologizing and the non-apologizing opponents, respectively, suggesting that female participants had enhanced implicit attitude towards the apologizing opponent. Furthermore, the late positive component (LPP) in brain potentials, a component associated with affective/motivational reactions, was larger for viewing the portrait of the apologizing than the non-apologizing opponent when participants subsequently selected low punishment. Additionally, the LPP elicited by the apologizing opponents’ portrait was larger in the female than in the male participants. These findings confirm the apology’s role in reducing reactive aggression and further reveal that this forgiveness process engages, at least in female, an enhancement of the victim’s implicit attitude and a prosocial motivational change towards the offender.